2019
DOI: 10.2147/ijn.s215950
|View full text |Cite
|
Sign up to set email alerts
|

<p>Toxicity screening of two prevalent metal organic frameworks for therapeutic use in human lung epithelial cells</p>

Abstract: IntroductionThe flexibility and tunability of metal organic frameworks (MOFs), crystalline porous materials composed of a network of metal ions coordinated by organic ligands, confer their variety of applications as drug delivery systems or as sensing and imaging agents. However, such properties also add to the difficulty in ensuring their safe implementation when interaction with biological systems is considered.MethodsIn the current study, we used real-time sensorial strategies and cellular-based approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…The same trend was observed in studies of the correlation between the MOF hydrophobicity and their toxicity towards human lung epithelial cells. It was shown that the hydrophobic ZIF-8 particles were more toxic than the hydrophilic MIL-160 particles [ 23 ] (IC 50 values were 61 µg/mL and 433 µg/mL, respectively). At the same time, some of the observed MOF particles demonstrate moderate or high toxicity to a live system.…”
Section: Introductionmentioning
confidence: 99%
“…The same trend was observed in studies of the correlation between the MOF hydrophobicity and their toxicity towards human lung epithelial cells. It was shown that the hydrophobic ZIF-8 particles were more toxic than the hydrophilic MIL-160 particles [ 23 ] (IC 50 values were 61 µg/mL and 433 µg/mL, respectively). At the same time, some of the observed MOF particles demonstrate moderate or high toxicity to a live system.…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes are shown in Figure 9. This study demonstrated the importance of screening toxicity before biomedical applications of MOFs [47].…”
Section: Biocompatibilitymentioning
confidence: 69%
“…Indeed, MOF biocompatibility is affected by the type of metal and ligand used in MOF structure. MOF physicochemical properties such as particle size, structure, and hydrophobicity can also be effective on MOF biocompatibility [34,36,47]. [41]).…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Wagner et al [414] tested in a model-way the toxicity of a MIL-160, a microporous hydrophilic aluminium-based MOF with a five-membered ring and an oxygen heteroatom, and ZIF-8, a hydrophobic framework of zeolitic imidazolate on the human bronchial epithelial (BEAS-2B) cells.…”
Section: Separatorsmentioning
confidence: 99%